Distribution of Microplastic at Sediment on Balikpapan Coastal Area - Marita Wulandari; Asri Prasaningtyas; Muhammad Ma'arij Harfadli; Anggi Melinda Handayani (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2021)
Coastal areas are often in the spotlight related to environmental problems, such as plastic waste. Coastal and coastal areas often face complex problems related to plastic waste, including microplastics. Microplastics (MPs) are tiny pieces of plastic that are as small as ≤ 5 mm and possibly pollute the environment. The study aimed to identify the presence and abundance of microplastics contaminating the coastal areas of Balikpapan City. Sediment samples were taken at a depth 0-10 cm. The observations were carried out in several stages; those stages are the drying stage, volume reduction, density separation, and counting using a microscope. The microplastic observation results with the microscope showed four types: fragment-shaped microplastics, phylum-shaped microplastics, fiber microplastics, and microbead-shaped microplastics. The highest number of microplastic particles was found at the Kampung Atas Air point, about 201 particles / 100 grams of dry sediment and the least number of microplastic particles were found at the Monpera point, about 16 particles / 100 grams of dry sediment. Microplastics with fiber form dominated all the study areas. Environmental conditions and pollutant sources influence the difference in the number of microplastics